Recurrent Cholesteatoma With Massive Extension to Temporoparietal Scalp: Case Report and Literature Review. (November 2014) - Zhu, Vivian F.; Isaacson, Brandon; Mull, Jason; Myers, Larry L.
Background: Cholesteatomas are locally destructive collections of epithelial debris arising from temporal bone squamous epithelium. Recurrences may occur after removal and are typically located within the temporal bone. Objective: This study aimed to report a case of a massive, recurrent cholesteatoma with extension to temporoparietal scalp in a 37-year-old woman. Methods: Case report with literature review. Results: The patient underwent complete excision of a well-circumscribed left temporal mass, intraoperatively identified to arise from the middle ear and to contain keratin debris. Conclusion: We report a case of recurrent cholesteatoma with massive extension to temporoparietal scalp. Clinical suspicion of recurrent cholesteatoma should remain in the differential diagnosis of temporal mass with prior history of cholesteatoma.